Avaliação do reconhecimento de faces em pacientes com a Doença de Alzheimer - Brito, Bruno da Silva (2018)
Significant increasing of senescence related diseases such as neoplasia, osteoporosis and, particularly, neurodegenerative diseases is noticed with raises in life expectancy. Alzheimer Disease (DA), for instance, has been of interest to health science researchers and professionals due to its cognitive disorder, including prosopagnosia which comprises the disability in familiar face recognition such as of family members and friends. Face recognition tests are applied to diagnose prosopagnosia in which the ethnic-racial profile of the population is usually not taken under consideration. The present study aimed to evaluate the face recognition response of DA patients using images of Brazilian individuals that are available in the Brazilian Test of Face Recognition (TRFBr). Twenty-two DA patients and 25 healthy elderly patients from João Pessoa, Paraíba were examined. Healthy Group of patients exhibited 53.76 mean (SD= 3.91) while the Alzheimer Group of patients 27.54 mean (SD= 6,78) in the test. It was also verified that the timeframe of face recognition response in the Alzheimer patients for the TRFBr (r = -,445 p < 0,05) is high and concurrent to low score for the Mini-Mental State Examination. Furthermore, self-perception of the impaired ability in face recognition is consistent as the disease evolves in the Alzheimer patients. This study thus supports that the early stages of the Alzheimer disease already put in jeopardy the ability of face recognition.